Gamification for psychomotor development: an experience with Genially in pre-school education - Núñez-Naranjo, Aracelly Fernanda; Acuña Mayorga, José Miguel; Viviana Lourdes Martinez (My University, 2024)
Psychomotor skills in early childhood are notably affected due to the pandemic, which is why the objective of the research was to implement gamified strategies in Genially that seek to improve psychomotor development in early education, the research had a mixed and field approach, with a proposal in which 21 students participated for 4 weeks; before the application of the proposal and after it, tests were applied, where the results obtained fulfilled the expectations of improvement in the teaching process.
Keywords: early education; gamification; Genially; psychomotricity; strategies